A novel countermeasure for preventing scour around monopile foundations using Ionic Soil Stabilizer solidified slurry. (April 2022) - Hu, Ruigeng; Lu, Yao; Leng, Hao; Liu, Hongjun; Shi, Wei
Highlights: A novel scour mitigation countermeasure of using the Ionic Soil Stabilizer (ISS) solidified slurry was investigated. The scour morphology and the performance of ISS solidified seabed were analyzed respectively. The scour protection mechanism of ISS solidified slurry was clarified by a series tests. The performance of the ISS-solidified slurry as scour protection layer was remarked comprehensively. Abstract: A novel scour prevention countermeasure of using the Ionic Soil Stabilizer (ISS) solidified slurry was investigated in this study. The ISS-solidified slurry is composed of Ionic Soil Stabilizer, Dispersion Resistance Agent (DRA), silt (or silty clay) and distilled water. It can be placed on the seabed immediately after monopile was installed, or in the developed scour holes. In present study, the first type was adopted as the scour protection layer around monopile. The scour morphology and the performance of scour protection layer was firstly analyzed based on flume experimental results. Furthermore, the falling head permeability tests, Zeta potential tests and scanning electron microscope (SEM) tests were carried out to investigate the scour protection mechanism of ISS-solidified slurry. Finally, the performance of the ISS-solidified slurry as scour protection layer was remarked comprehensively. The results indicate that the ISS-solidified slurry for scour protection is favorable and cost-effectiveness. Compared with the untreated seabed, the ISS-solidified slurry layer can bear with the greater critical shear stress required for the initial scour. The DRA can keep the fluidity of ISS-solidified slurry within an appropriate range and facilitate the hardening process in water simultaneously, so the DRA is indispensable for ISS-solidified slurry when it is used as scour protection layer in field. Graphical abstract: Image, graphical abstract